PENGARUH LINGKUNGAN WAJIB PAJAK, KONTROL KEPERILAKUAN YANG DIPERSEPSIKAN DAN KEWAJIBAN MORAL TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KELURAHAN PAAL DUA MANADO - Kawengian, Pricillia V.E; Sabijono, Harijanto; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Taxpayer Compliance is an obedient attitude of the taxpayer in carrying out the provisions and tax regulations that are required and should be implemented. Taxpayer compliance may be influenced by the taxpayer's environment, perceived behavioral control and moral obligations. The population in this research is Individual Taxpayer in Kelurahan Paal Dua Manado. The sample in this research is 50 respondents with sampling technique using incidental sampling technique. Methods of collecting data with questionnaires. This study used multiple linear regression method with the help of SPSS. The results show that the taxpayer Environment () and Moral Obligations () have an influence on taxpayer compliance (Y). Perceived Behavioral Control () has no effect on taxpayer compliance (Y).Keywords: taxpayer environment, Perceived Behavioral Control, Moral Obligations and taxpayer compliance.